Alpha-diimine nickel complex, synthetic method and application

By designing α-diimine nickel complexes, combining electrons and stereosubstituted groups, the chain entanglement and low branching problems of catalysts in the preparation of ultra-high molecular weight polyethylene are solved, and a high-efficiency and low-cost catalytic effect is achieved. And improve the thermal stability and mechanical properties of the catalyst.

CN119161392AActive Publication Date: 2024-12-20ZHENGZHOU UNIV
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202410765615.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-14
Publication Date
2024-12-20
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

When preparing ultra-high molecular weight polyethylene, existing catalysts have problems such as chain entanglement, low branching degree and high molecular weight distribution, which leads to increased processing difficulty and high production costs, and insufficient thermal stability of the catalyst, making it difficult to meet industrial needs.

Method used

Using α-diimine nickel complex as catalyst, by combining electron substituents and stereosubstitutes, the steric steric hindrance and electron effects of the catalyst are optimized, the ethylene insertion rate and the chain transfer rate are inhibited, and the large steric hindered dibenzo is combined. The electron substituents of the barrel ene skeleton and aniline are designed to design catalysts with high activity and high heat stability.

Benefits of technology

It realizes efficient catalytic ethylene polymerization, producing ultra-high molecular weight polyethylene and POE with high molecular weight, low branching degree and narrow molecular weight distribution. It has excellent mechanical properties and high thermal stability, can maintain high activity at 120℃, and reduces production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161392A_ABST
    Figure CN119161392A_ABST
Patent Text Reader

Abstract

The invention provides an alpha-diimine nickel complex as well as a synthesis method and application thereof, the alpha-diimine nickel complex is used for preparing a high-thermal-stability catalyst of an ultra-high molecular weight polyethylene thermoplastic elastomer and a POE (Polyolefin Elastomer) material, and the structural formula of the alpha-diimine nickel complex is as shown in formula (I). The alpha-diimine nickel complex has high catalytic activity in catalysis of ethylene polymerization and has good thermal stability. The molecular weight distribution of the obtained ultra-high molecular weight polyethylene is 1.3-2.5, the molecular weight is 79-833 * 10 < 4 > g.mol <-1 >, the ultra-high molecular weight polyethylene shows good tolerance in catalysis of ethylene and polar monomer copolymerization, ultra-high molecular weight polar polyethylene can be produced, and the ultra-high molecular weight polyethylene can also be used for catalyzing ethylene and 1-octylene copolymerization to prepare POE (Polyolefin Elastomer) for polymer compatibilization blending. The obtained ultra-high molecular weight polyethylene elastomer has good physical and mechanical properties. The catalyst has ultrahigh catalytic activity, the production cost of the catalyst can be greatly reduced, high-performance polyethylene can be produced, and the catalyst has great industrial application potential. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of olefin coordination polymerization catalysts and polyolefins, and particularly relates to an ultra-high activity catalyst alpha-diimine nickel complex for synthesizing ultra-high molecular weight polyethylene thermoplastic elastomer, a synthesis method and application thereof. Background Art

[0002] As one of the high-end polyolefins, ultra-high molecular weight polyethylene and POE have many excellent properties. The former has the characteristics of chemical corrosion resistance, weather resistance, wear resistance, impact resistance, self-lubrication, etc., and has been widely used in biomedicine, military equipment, diaphragm batteries and other industries. The latter is widely used in the photovoltaic industry, PP, PE capacity expansion and blending industries due to its advantages of low relative density, easy processing and molding, good mechanical properties, chemical resistance and water resistance.

[0003] At present, 70% of the UHMWPE produced in the world's industry still uses supported ZN catalysts. This type of catalyst contains multiple active sites, and these active sites show different reactivity, which is easy to produce polymers with a wide molecular weight distribution (about 5 to 20); the polymer growth chains are close to each other, which increases the possibility of chain entanglement. This chain entanglement and ultra-low branching degree (less than one in 100,000) make it difficult to process using traditional processing technology. Therefore, it is still necessary to change the type of electron donor and carrier of the ZN catalyst to further optimize its catalytic performance. For metallocene catalysts, under appropriate conditions, there are few metallocene complexes that can achieve ultra-high molecular weight polyethylene. In addition, a large amount of excess MAO activator is often required to be added when preparing polyethylene, which undoubtedly increases the production cost. Therefore, reducing the cost of use and simplifying the process have become the focus of research on this type of catalyst. Non-metallocene late transition catalysts have gradually become a hot topic of research due to their low price, environmental friendliness, stability and easy availability; through the design and synthesis of ligands, researchers can achieve precise regulation of polymer structure and obtain UHMWPE with high molecular weight, narrow distribution, disentanglement and low branching. However, one or more of the following principles should be combined in catalyst design: (a) the metal center should have high electrophilicity, (b) the chain transfer rate should be as low as possible, (c) the ligands around the metal must endow the catalytic center with an appropriate balance of electronic and steric effects to maximize the ethylene insertion rate and suppress the chain transfer rate, and (d) pressure and temperature also play an important role. Therefore, it is quite challenging to produce such high molecular weight polyethylene by repeated insertion of ethylene.

[0004] Polyolefin elastomer (POE) is a polymer produced by copolymerization of ethylene and α-olefins, and was first introduced to the market by the Dow Chemical Company in the United States in 1994. Due to factors such as the technical barriers of catalysts, the lack of polymerization processes, and the supply of raw materials α-olefins, my country's current consumption products mainly rely on imports, so in-depth research on POE is still needed.

[0005] In 2020, Professor Jian Zhongbao's research group designed an α-diimine catalyst with a double-layer space strategy. By combining it with a methylaluminoxane activator, it can prepare ultra-high molecular weight polyethylene with a molecular weight of up to 467×10 4 g·mol -1 (J.Catal., 2020, 390, 30-36, CN 111548285 A); In 2021, Professor Dai Shengyu's research group used the dual steric hindrance effect to prepare a catalyst with higher stability, which can produce ultra-high branched polyethylene with higher molecular weight (M w =127.3 g mol -1 , branching degree: 80-150 / 1000C)(Organometallics, 2022, 41, 124-132, CN114349658 A); after that, the catalyst combining the large steric hindrance of diphenylmethyl substituent and benzocycloalkyl was also designed by the research group, which further improved the catalytic activity (10 7 g mol -1 h -1 ), and prepared ultra-high molecular weight polyethylene (M w =185×10 4 g mol -1 ), but it also leads to a higher molecular weight distribution (Polym.Chem., 2023, 14, 183-190); in 2023, Professor Sun Wenhua's research group combined the large steric hindrance diphenylmethyl substituent with the flexible cycloalkyl substituent to prepare polyethylene with ultra-high molecular weight (Molecules, 2023, 28, 4852-4872, CN 116396338 A), and the stereo substituent and the electronic substituent synergized to improve the performance of the catalyst. The introduction of three methoxy groups significantly improved the chain growth rate and promoted the synthesis of ultra-high molecular weight polyethylene (M w =126×10 4 g mol -1). (Polymer, 2024, 293, 126690-126703); Patent CN 103288985 A also discloses the copolymerization of ethylene and α-olefins to obtain elastic polymers with higher molecular weight; Patent CN 115594785A is capable of preparing POE polymers with high 1-octene content with high activity.

[0006] In summary, producing high-performance polyolefins has become a solution to solve the shortcomings of high costs and insufficient competitiveness of the domestic industry. Therefore, it is urgent to develop a type of catalyst to catalyze the production of functionalized high-end polyethylene. Summary of the invention

[0007] In order to improve the activity of the catalyst, produce high-performance high-end polyolefins, and increase the molecular weight and insertion ratio of the copolymerization product of ethylene and polar monomers, the present invention provides an α-diimine nickel complex, a synthesis method and an application thereof. The α-diimine nickel complex is a late transition metal nickel catalyst in which a series of electronic substituents and stereo substituents are combined.

[0008] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows:

[0009] The α-diimine nickel complex has a chemical structure shown in formula (I):

[0010]

[0011] Where R 1 is one of diphenylmethyl, phenyl, 3,5-difluorophenyl, 3,5-dimethylphenyl, 3,5-ditrifluoromethylphenyl, R 2 is one of halogen, alkyl, and alkoxy;

[0012] Preferably, the α-diimine nickel complex of the chemical structure shown in formula (I) comprises at least one of I1 to I7:

[0013]

[0014] More preferably, the α-diimine nickel complexes with the chemical structure shown in formula (I) are I2 and I7.

[0015] The present invention provides a method for synthesizing an α-diimine nickel complex having a chemical structure shown in formula (I), comprising the following steps:

[0016] (1) The dibenzo-barrelene represented by formula (II) and the aniline compound represented by formula (III) are reacted at 130° C. for 12 to 36 hours under the catalysis of zinc dichloride to obtain an α-diimine compound represented by formula (IV). The reaction scheme is as follows:

[0017]

[0018] Where R 1 is one of diphenylmethyl, phenyl, 3,5-difluorophenyl, 3,5-dimethylphenyl, 3,5-ditrifluoromethylphenyl, 3,5-di-tert-butylphenyl, R 2 is one of halogen and alkoxy;

[0019] (2) reacting the α-diimine compound represented by formula (IV) with (DME)NiBr2 at 0 to 45°C for 1 to 50 hours to generate an α-diimine nickel complex having a chemical structure represented by formula (I);

[0020] The present invention provides a method for synthesizing an α-diimine nickel complex having a chemical structure shown in formula (I), wherein the molar ratio of the compound of formula (II) to the aniline compound shown in formula (III) is 1:(2-3).

[0021] In the synthesis method of the α-diimine nickel complex of the chemical structure shown in formula (I) provided by the present invention, the α-diimine compound shown in formula (IV) reacts with (DME)NiBr2 in an organic solvent, and the organic solvent is an organic solvent well known to those skilled in the art, preferably a halogenated alkane, more preferably dichloromethane. The molar ratio of the α-diimine compound to (DME)NiBr2 is 1:(0.1-6). In a specific embodiment, the molar ratio of the α-diimine compound to (DME)NiBr2 is 1:(1-3). Preferably, the reaction is carried out at 0°C to 38°C, and the reaction time is 12-24h.

[0022] The present invention also provides an application of an α-diimine nickel complex having a chemical structure shown in formula (I) in the synthesis of polyolefins, specifically: the α-diimine nickel complex is used as an ultra-high activity and highly thermally stable catalyst to catalyze ethylene polymerization to prepare an ultra-high molecular weight polyethylene thermoplastic elastomer and POE material.

[0023] In some embodiments provided by the present invention, the application includes: contacting a terminal olefinic compound with an α-diimine nickel complex having a chemical structure shown in formula (I) and an alkyl aluminum reagent, and the terminal olefinic compound undergoes a homopolymerization reaction. In this application, the homopolymerization reaction is carried out in an organic solvent, the amount of the α-diimine nickel complex is 5 to 40 μmol / L, the temperature of the homopolymerization reaction is 0°C to 150°C, the pressure is 0.1 to 2.0 MPa, and the reaction time is 0.05 to 3.00 hours.

[0024] More preferably, the concentration of the α-diimine nickel complex is 20 μmol / L, the homopolymerization temperature is 30° C., the pressure is 0.8 MPa, and the reaction time is 10 minutes to obtain the best catalytic effect.

[0025] In some embodiments provided by the present invention, the application includes: contacting a terminal olefinic compound, a polar monomer, an α-diimine nickel complex having a chemical structure shown in formula (I), and an alkyl aluminum reagent, and copolymerizing the terminal olefinic compound with the polar monomer; the polar monomer refers to an olefin containing a heteroatom, including at least one of 10-undecenoic acid methyl ester, methyl acrylate, vinyltrimethoxysilane, propylene acetate, methyl borneol, 1-octene, 6-chloro-1-hexene, 10-undecenol, etc. In this application, the copolymerization temperature is 0 to 50°C, the copolymerization pressure is 0.1 to 1MPa, and the reaction time is 0.05 to 3.00 hours. The concentration of the α-diimine nickel complex is 200 to 400 μmol / L, and the monomer concentration is 0.1 to 3.0M.

[0026] More preferably, 400 μmol / L of catalyst I7 is polymerized with 3.0 M 1-octene at 30° C. and 0.2 MPa for 30 min to prepare high-performance polyethylene (POE), whose strain performance is up to 2300% and elastic recovery rate is 71%.

[0027] Preferably, in the above application, the compound containing a terminal olefin group is an olefin, more preferably ethylene, and the alkyl aluminum reagent includes one or more of MAO, MMAO, AlMe3, AlEtCl2, AlEt2Cl, and AlEt3.

[0028] The above α-diimine nickel complex, on the one hand, inhibits chain transfer by increasing steric hindrance, thereby improving the thermal stability of the catalyst and the molecular weight of the polymer; on the other hand, it utilizes the electronic substituents on aniline to enhance the catalyst activity; the α-diimine nickel complex maintains a high catalytic activity in the copolymerization reaction of ethylene and various polar monomers.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] The α-diimine nickel complex of the chemical structure shown in formula (I) provided by the present invention fully inhibits chain transfer due to the rigid dibenzobarrelene skeleton and the introduction of a large sterically hindered aromatic group on aniline; and the activity of the catalyst is greatly enhanced by adjusting the different electrical substituents on the para position of aniline and the aromatic substituent, and can efficiently catalyze ethylene polymerization, improve catalytic activity, and simultaneously produce ultra-high molecular weight polyethylene, POE and other high-end polyolefins, and can effectively catalyze the copolymerization of ethylene and various polar monomers to produce polar functionalized polyethylene.

[0031] The catalytic activity of the α-diimine nickel complex in ethylene polymerization can reach 1.0×10 8 g·mol -1 ·h -1Theoretically, 1kg of catalyst can produce 2.54 thousand tons of product, and it can still maintain 10 6 g·mol -1 ·h -1 The catalyst can also produce ultra-high molecular weight polyethylene (79-833×10 4 g·mol -1 ); it also has a low degree of branching (15-41 / 1000C) and excellent mechanical properties (stress: 2.5-43MPa, strain: 170%-2280%); and it can also maintain good catalytic activity (up to 13.34×10 5 g·mol -1 ·h -1 ) and a higher insertion ratio (1-octene insertion rate can reach 13.34%), producing POE polymers or polar functionalized polyolefins.

[0032] During olefin polymerization, I1-I7 utilized the large steric hindrance of dibenzo-barrel ene skeleton to shield the steric hindrance on the back of the metal. At the same time, the large ortho-aromatic substituents in the three-dimensional space inhibited chain transfer, reduced the molecular weight distribution of the polymer, and greatly increased the molecular weight of the polymer. The ultra-high molecular weight polyethylene catalyzed by I2 was as high as 833.3×10 4 g·mol -1 , before this, catalysts that can prepare such high molecular weight polyethylene are extremely rare. As the temperature increases, the introduction of these large sterically hindered aromatic substituents greatly enhances the stability of the nickel complex; and I1 can still be highly active at 120°C with a concentration of 7.32×10 6 g·mol -1 ·h -1 The catalytic performance of ethylene polymerization is well demonstrated by the high thermal stability of this type of catalyst. I2, I3, I5 and I7 introduce electron-withdrawing groups at different positions of different benzene rings, which greatly improves the activity of the catalyst. In addition, by adjusting the polymerization reaction conditions such as temperature and pressure, the maximum activity of the catalyst can reach 1.0×10 8 g·mol -1 ·h -1 (Application Example 14). Theoretically, 1 kg of catalyst can produce 2.54 thousand tons of product. More interestingly, I1-3 and I5 can prepare ultra-high molecular weight thermoplastic elastomers. The stress value of ultra-high molecular weight thermoplastic elastomer prepared by I1 at 50 ° C can reach 43 MPa, and the polyethylene prepared by I2 at 70 ° C can maintain an ultra-high molecular weight (833.3×10 4 g·mol -1) and has good tensile properties (maximum strain can reach 770%). By introducing different electronic groups at the ortho or para position of benzene, the elimination of β-H can be well suppressed, and the activity and molecular weight of the catalyst can be improved.

[0033] Moreover, catalysts I1-3 and I7 can copolymerize with a variety of polar monomers to produce functionalized polyolefins. In addition, I7 can also copolymerize with 1-octene to prepare high-performance polyethylene (POE), whose strain performance can reach 2300% and elastic recovery rate can reach 71%. Therefore, the α-diimine nickel complex provided by the present invention has great potential in the field of olefin polymerization to synthesize high-end polyolefins such as ultra-high molecular weight polyethylene and POE. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 This is a single crystal structure diagram of the α-diimine nickel complex I1 provided in Example 8 of the present invention.

[0036] Figure 2 A single crystal structure diagram of α-diimine nickel complex I2 is provided for Example 9 of the present invention.

[0037] Figure 3 This is a single crystal structure diagram of the α-diimine nickel complex I3 provided in Example 10 of the present invention.

[0038] Figure 4 This is an image of the stretching curve of polyethylene prepared by the α-diimine nickel complex I1 provided in Application Examples 1 to 5 of the present invention.

[0039] Figure 5 This is an image of the polyethylene tensile curve prepared by the α-diimine nickel complex I2 provided in Example 9 of the present invention.

[0040] Figure 6 This is an image of the stretching curve of polyethylene prepared using the α-diimine nickel complex I3 provided in Example 10 of the present invention.

[0041] Figure 7 This is an image of the POE stretching curve prepared by the α-diimine nickel complex I7 provided in Application Examples 47, 48, and 49 of the present invention.

[0042] Figure 8 This is an image of POE elastic recovery prepared using the α-diimine nickel complex I7 provided in Application Example 47 of the present invention.

[0043] Fig. 9 This is an image of POE elastic recovery prepared using the α-diimine nickel complex I7 provided in Application Example 48 of the present invention.

[0044] Fig.10 This is an image of POE elastic recovery prepared using the α-diimine nickel complex I7 provided in Application Example 49 of the present invention. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] In the present invention, the term "DME" represents ethylene glycol dimethyl ether; the term "terminal olefin-containing compound" refers to a small molecule organic compound with a C=C double bond at the end, including olefins, fatty acids containing terminal olefins, esters, etc. In the α-diimine nickel complex, the "—" connected to Ni refers to a covalent bond or a coordination bond.

[0047] Unless otherwise specified, the processes of homopolymerization and copolymerization are well known to those skilled in the art and will not be described in detail here.

[0048] The following examples of the present invention show different aspects of the present invention. The data given include the synthesis of the ligand, the synthesis of the metal complex, the polymerization operation, the polymerization conditions and the polymerization product. All operations including reactions, preparations and storage were carried out under a dry inert atmosphere using standard Schlenk operations. Molecular weight and molecular weight distribution were determined by GPC. The determination was carried out on an Agilent PL-200 instrument using trichlorobenzene as solvent and Agilent PLgel Olexis as chromatographic column. Polystyrene was used as the standard and polyethylene was calibrated by universal calibration using Mark-Houwink parameters: K = 1.75 × 10 -2 cm 3 / g, R = 0.67 (polystyrene), K = 5.90 × 10 -2 cm 3 / g, R=0.69 (polyethylene).

[0049] In the present invention, the preparation route of the α-diimine compound is as follows:

[0050]

[0051] Example 1

[0052] This embodiment provides a method for synthesizing α-diimine compound IV1. The steps include:

[0053] In a 50mL Shrek bottle, add dibenzo-barrelene (469mg, 2mmol), 2-dibenzhydryl-4-methoxy-6-methylaniline (1.47g, 4.4mmol), zinc dichloride (272mg, 2mmol), and 5mL glacial acetic acid, and heat to 130℃ and reflux for 24h. After the reaction is completed, cool to room temperature, and a yellow precipitate precipitates from the reaction system. Filter the yellow precipitate, wash with glacial acetic acid and ether, and the obtained solid is the zinc dichloride complex of IV1. Dissolve the above-obtained solid in 50mL dichloromethane, add potassium oxalate (536mg, 4mmol) aqueous solution (10ml) and stir for 12h, extract the organic layer with dichloromethane (50mL×3), dry with anhydrous sodium sulfate, and remove the solvent by vacuum distillation to obtain a yellow solid as a crude product. The crude product was recrystallized from a mixed solution of dichloromethane and methanol to obtain a yellow solid as pure α-diimine compound IV1, 1.48 g (92%). Experimental data of the compound: 1 H NMR(400MHz, CDCl3)δ=7.24–7.16(m,10H,aryl-H),7.11–7.04(m,10H,aryl-H),6. 94(dd,J=7.5,2.0Hz,4H,aryl-H),6.76(d,J=2.4Hz,2H,aryl-H),6.69(dd,J=5.4,3 .2Hz,2H,aryl-H),6.62(d,J=2.8Hz,2H,aryl-H),6.31(dd,J=5.4,3.2Hz,2H,aryl -H),5.43(s,2H,CHPh2),4.83(s,2H,CHDB),3.77(s,6H,CH3),1.90(s,6H,CH3)ppm. 13 C{ 1 H}NMR (101MHz, CDCl3) δ = 161.02 (C = N), 155.64, 144.46, 142.74, 140.64, 138.77, 137.70, 134.20, 129.48, 129.14, 128.43, 128.06, 12 7.15,127.04,126.80,126.38,125.95,125.78,124.32,114.28,113.54,55.25(OCH3),51.30(CHDB),51.12(CHPh2),19.00(CH3)ppm.

[0054] Example 2

[0055] This embodiment provides a method for synthesizing α-diimine compound IV2. The steps include:

[0056] In a 50mL Shrek bottle, add dibenzo-barrelene (469mg, 2mmol) of formula (II), 2-dibenzhydryl-4-fluoro-6-methylaniline (1.28g, 4.4mmol), zinc dichloride (272mg, 2mmol), and 5mL glacial acetic acid, and heat to 130℃ and reflux for 24h. After the reaction is completed, cool to room temperature, and a yellow precipitate precipitates from the reaction system. Filter the yellow precipitate, wash with glacial acetic acid and ether, and the obtained solid is the zinc dichloride complex of IV2. Dissolve the above-obtained solid in 50mL of dichloromethane, add potassium oxalate (536mg, 4mmol) aqueous solution (10ml) and stir for 12h, extract the organic layer with dichloromethane (50mL×3), dry with anhydrous sodium sulfate, and remove the solvent by vacuum distillation to obtain a yellow solid as a crude product. The crude product is recrystallized in a mixed solution of dichloromethane and methanol to obtain a yellow solid as a pure α-diimine compound IV2, 1.45g (93%). Experimental data of this compound: 1 H NMR (400MHz, CDCl3) δ=7.25–7.20(m,10H,aryl-H),7.10–7.06(m,10H,aryl-H),6.93–6.89(m,6H,aryl-H),6.78(d,J=2.9Hz,1H,aryl-H),6.76(d,J=2.8 Hz,1H,aryl-H),6.72(dd,J=5.4,3.1Hz,2H,aryl-H),6.32(dd,J=5.4,3.3Hz,2H,aryl-H),5.39(s,2H,2CHPh2),4.79(s,2H,CHDB),1.89(s,6H,CH3)ppm. 13 C{1H}NMR(101MHz, CDCl3)δ=160.89(C=N),159.01(d, 1 J C-F =242.2Hz),143.62,142.60,141.87,138.11,137.05,134.33,134.26,129.08,128.73,128.31,127.91,127.34(d, 3 J C-F =7.8Hz),127.05(d, 3 J C-F=16.5Hz),126.36 125.94,125.50,124.09,115.14,114.92 114.83,114.60,51.02(CHDB),50.78(CHPh2),18.45(CH3)ppm. 19 F NMR (376MHz, CDCl3) δ = -120.22 (t, J = 9.3Hz) ppm.

[0057] Example 3

[0058] This embodiment provides a method for synthesizing α-diimine compound IV3. The steps include:

[0059] In a 50mL Shrek bottle, add formula (II) (469mg, 2mmol), 2-dibenzhydryl-4-chloro-6-methylaniline (1.35g, 4.4mmol), zinc dichloride (272mg, 2mmol), and 5mL glacial acetic acid, and heat to 130℃ and reflux for 24h. After the reaction is completed, cool to room temperature, and a yellow precipitate precipitates from the reaction system. Filter the yellow precipitate, wash with glacial acetic acid and ether, and the obtained solid is the zinc dichloride complex of IV3. Dissolve the above-obtained solid in 50mL dichloromethane, add potassium oxalate (536mg, 4mmol) aqueous solution (10ml) and stir for 12h, extract the organic layer with dichloromethane (50mL×3), dry with anhydrous sodium sulfate, and remove the solvent by vacuum distillation to obtain a yellow solid as a crude product. The crude product is recrystallized in a mixed solution of dichloromethane and methanol to obtain a yellow solid as a pure α-diimine compound IV3, 1.48g (91%). Experimental data of this compound: 1 H NMR (400MHz, CDCl3) δ=7.24–7.18(m,12H,aryl-H),7.08–7.06(m,10H,aryl-H),7.01(d,J=2.3Hz,2H aryl-H),6.89(dd,J=6.5,2.8Hz,2H,aryl-H),6.72(dd,J=5.4,3.3Hz,4H,aryl-H),aryl-H),6.31(dd,J=5.4,3.3Hz,2H aryl-H),5.35(s,2H,CHPh2),4.75(s,2H,CHDB),1.86(s,6H,CH3)ppm. 13 C{ 1H}NMR (101MHz, CDCl3) δ = 160.66 (C = N), 158.22, 145.22, 143.47, 141.70, 137.95, 136.88, 134.22, 129.09, 128.73, 128 .35,127.95,127.34,127.23,127.06,126.41,126.00,125.52,124.12,51.06(CHDB),50.71(CHPh2),18.19(CH3)ppm.

[0060] Example 4

[0061] This embodiment provides a method for synthesizing α-diimine compound IV4. The steps include:

[0062] In a 50mL Shrek bottle, add formula (II) (469mg, 2mmol), 3,5-dimethyl-[1,1']biphenyl-2-amine (0.87g, 4.4mmol), zinc dichloride (272mg, 2mmol), and 5mL glacial acetic acid, and heat to 130℃ and reflux for 24h. After the reaction is completed, cool to room temperature, and a yellow precipitate precipitates from the reaction system. Filter the yellow precipitate, wash with glacial acetic acid and ether, and the obtained solid is the zinc dichloride complex of IV4. Dissolve the above-obtained solid in 50mL dichloromethane, add potassium oxalate (536mg, 4mmol) aqueous solution (10ml) and stir for 12h, extract the organic layer with dichloromethane (50mL×3), dry with anhydrous sodium sulfate, and remove the solvent by vacuum distillation to obtain a yellow solid as a crude product. The crude product is recrystallized in a mixed solution of dichloromethane and methanol to obtain a yellow solid as a pure α-diimine compound IV4, 1.12g (95%). Experimental data of this compound: 1H NMR (600MHz, CDCl3) Isomer 1: δ = 7.53–7.51 (m, 4H aryl-H),7.24(s,2H,aryl-H),7.07–7.04(m,8H,aryl-H),6.96–6.93(m,4H,aryl-H),6.78(td,J=7.5,1.2Hz,2H,ar Isomer 2:7.41–7.39(m,1H,aryl-H),7.16(s,0.5H,aryl-H),7.12(dd,J=5.5,3.2Hz,0.5H,aryl-H),7.08(s,0.5H,aryl-H),6.88–6.87(m,2H,aryl-H),6.7 5(dd,J=5.5,3.2Hz,0.5H,aryl-H),6.53(dd,J=5.5,3.2Hz,0.5H,aryl-H),4.71(s,0.5H,CHDB),2.42(s,6H,aryl-CH3),1.80(s,6H,aryl-CH3)ppm. 13 C{ 1 H}NMR (151MHz, CDCl3) Isomer 1: δ = 158.45, 139.06, 137.14, 136.70, 133.32, 130.10, 129.55, 129.17, 128.25, 127.62 127.27,126.83,126.76,126.35,125.11,123.79,50.78,20.96,18.09ppm.Isomer 2:159.19(C=N),144.16,139.29,138.29,136.25,133.24,130.22,130.17,128.93,128.59 ,129.73,127.33,127.13,126.51,126.26,124.88,124.55,51.04(CHDB),20.89,18.07ppm.

[0063] Example 5

[0064] This embodiment provides a method for synthesizing α-diimine compound IV5. The steps include:

[0065] In a 50mL Shrek bottle, add formula (II) (469mg, 2mmol), 3',5'-difluoro-3,5-dimethyl-[1,1']biphenyl-2-amine (1.03g, 4.4mmol), zinc dichloride (272mg, 2mmol), and 5mL glacial acetic acid, and heat to 130℃ and reflux for 24h. After the reaction is completed, cool to room temperature, and a yellow precipitate precipitates from the reaction system. Filter the yellow precipitate, wash with glacial acetic acid and ether, and the obtained solid is the zinc dichloride complex of IV5. Dissolve the above-obtained solid in 50mL dichloromethane, add potassium oxalate (536mg, 4mmol) aqueous solution (10ml) and stir for 12h, extract the organic layer with dichloromethane (50mL×3), dry with anhydrous sodium sulfate, and remove the solvent by vacuum distillation to obtain a yellow solid as a crude product. The crude product was recrystallized from a mixed solution of dichloromethane and methanol to obtain a yellow solid as pure α-diimine compound IV5, 1.23 g (93%). Experimental data of the compound: 1 H NMR(600MHz, CDCl3)δ=7.17(s,2H,aryl-H),7.12(s,2H,aryl-H),7.04–7.01(m,6H,aryl-H),6.96–6.92(m,4H,aryl-H),6.64(d, J=7.3Hz,2H,aryl-H),6.37(tt,J=8.9,2.4Hz,2H,aryl-H),4.62(s,2H,CHDB),2.43(s,6H,aryl-CH3),1.87(s,6H,aryl-CH3)ppm. 13 C{ 1 H}NMR(151MHz,CDCl3)δ=162.51(dd,J C-F =246.7,13.2Hz),158.87(C=N),144.11,142.47(t,J C-F =9.8Hz),136.53,133.81,131.33,127.87,127.82,127.50,126.94,124.90,124.29,112.05(dd,J=20.9,5.4Hz),101.47(t,J C-F =25.4Hz),50.86(CHDB),20.89,17.91ppm. 19 F{ 1 H}NMR (565MHz, CDCl3) δ = -110.98ppm.

[0066] Example 6

[0067] This embodiment provides a method for synthesizing α-diimine compound IV6. The steps include:

[0068] In a 50mL Shrek bottle, add formula (II) (469mg, 2mmol), 3,3',5,5'-tetramethyl-[1,1']biphenyl-2-amine (0.99g, 4.4mmol), zinc dichloride (272mg, 2mmol), and 5mL glacial acetic acid, and heat to 130℃ and reflux for 24h. After the reaction is completed, cool to room temperature, and a yellow precipitate precipitates from the reaction system. Filter the yellow precipitate, wash with glacial acetic acid and ether, and the obtained solid is the zinc dichloride complex of IV6. Dissolve the above-obtained solid in 50mL dichloromethane, add potassium oxalate (536mg, 4mmol) aqueous solution (10ml) and stir for 12h, extract the organic layer with dichloromethane (50mL×3), dry with anhydrous sodium sulfate, and remove the solvent by vacuum distillation to obtain a yellow solid as a crude product. The crude product was recrystallized from a mixed solution of dichloromethane and methanol to obtain a yellow solid as pure α-diimine compound IV6, 1.22 g (94%). Experimental data of the compound: 1 H NMR (400MHz, CDCl3): isomer 1: δ=7.14(d,J=1.4Hz,1H,aryl-H),7.44(dd,J=2.0,1.3Hz,2H,aryl-H),7.31(dd,J=2.0,1.3Hz,2H,aryl-H),7.19(d,J=1.6Hz,1H,aryl- H),7.07-7.16(m,10H,aryl-H),6.83-7.04(m,2H,aryl-H),4.22(s,2H,CHDB),2.32(s,12H,CH3),2.27(s,6H,CH3),2.22(s,6H,CH3)ppm. 13 C{ 1 H}NMR (101MHz, CDCl3): δ=150.7,141.3,138.3,137.4,137.1,130.0,129.6, 128.9,128.5,128.0,126.6,126.2,123.9,116.8,51.8,21.3,21.6,18.6ppm.

[0069] Example 7

[0070] This embodiment provides a method for synthesizing α-diimine compound IV7. The steps include:

[0071] In a 50mL Shrek bottle, add formula (II) (469mg, 2mmol), 3',5'-ditrifluoromethyl-3,5-dimethyl-[1,1']biphenyl-2-amine (1.47g, 4.4mmol), zinc dichloride (272mg, 2mmol), and 5mL glacial acetic acid, and heat to 130℃ and reflux for 24h. After the reaction is completed, cool to room temperature, and a yellow precipitate precipitates from the reaction system. Filter the yellow precipitate, wash with glacial acetic acid and ether, and the obtained solid is the zinc dichloride complex of IV7. Dissolve the above-obtained solid in 50mL dichloromethane, add potassium oxalate (536mg, 4mmol) aqueous solution (10ml) and stir for 12h, extract the organic layer with dichloromethane (50mL×3), dry with anhydrous sodium sulfate, and remove the solvent by reduced pressure distillation to obtain a yellow solid as a crude product. The crude product was recrystallized from a mixed solution of dichloromethane and methanol to obtain a yellow solid as pure α-diimine compound IV7, 1.67 g (96%). Experimental data of the compound: 1 H NMR(600MHz, CDCl3)δ=7.83(s,4H,aryl-H)),7.54(s,2H,aryl-H),7.16(s,1H,aryl-H)),7.08(s,1H,aryl-H)),7.05–6.99(m,4H,aryl-H) )),6.89(t,J=7.4Hz,2H,aryl-H)),6.63(d,J=7.4Hz,2H,aryl-H),4.70(s,2H,CHDB),2.44(s,6H,aryl-CH3),1.75(s,6H,aryl-CH3)ppm. 13 C{ 1 H}NMR(151MHz, CDCl3)δ=160.36,143.93,142.02,136.88(d,J C-F =10.2Hz),134.21,131.87,131.14(q,J C-F =32.9Hz),129.02,128.89,127.82,127.64,127.62,127.35,124.91,124.44,123.24(q,J C-F =273.2Hz)120.45(q,J C-F =4.1Hz),51.13,20.78,18.00ppm. 19 F{ 1 H}NMR (565MHz, CDCl3) δ = -62.53ppm.

[0072] Example 8

[0073] This embodiment provides a method for synthesizing α-diimine nickel complex I1. The steps include:

[0074] In a glove box with argon atmosphere, add α-diimine compound IV1 (0.80 g, 1.00 mmol), (DME)NiBr2 (0.31 g, 1.00 mmol), and 10 mL of anhydrous dichloromethane prepared in Example 1 to a 50 mL round-bottom flask and stir at room temperature for 24 h. After the reaction is completed, filter the reaction system using a sand core funnel and remove the solvent in vacuo. Recrystallize in dichloromethane and n-hexane solution to obtain a reddish brown solid, which is complex I1, 0.98 g (95%). Experimental data of α-diimine nickel complex I1: ESI-MS (m / z): [M-Br] + Calculate for C 58 H 48 BrN2NiO2 + , 941.2253.

[0075] Example 9

[0076] This embodiment provides a method for synthesizing α-diimine nickel complex I2. The steps include:

[0077] In a glove box with argon atmosphere, add α-diimine compound IV2 (0.78 g, 1.00 mmol), (DME)NiBr2 (0.31 g, 1.00 mmol), and 10 mL of anhydrous dichloromethane prepared in Example 1 to a 50 mL round-bottom flask and stir at room temperature for 24 h. After the reaction is completed, filter the reaction system using a sand core funnel and remove the solvent in vacuo. Recrystallize in dichloromethane and n-hexane solution to obtain a reddish brown solid, namely complex I2, 1.09 g (93%). Experimental data of α-diimine nickel complex I2: ESI-MS (m / z): [M-Br] + Calculate for C 56 H 42 BrN2NiF2 + , 917.1853.

[0078] Example 10

[0079] This embodiment provides a method for synthesizing α-diimine nickel complex I3. The steps include:

[0080] In a glove box with argon atmosphere, add α-diimine compound IV3 (0.81 g, 1.00 mmol), (DME)NiBr2 (0.31 g, 1.00 mmol), and 10 mL of anhydrous dichloromethane prepared in Example 1 to a 50 mL round-bottom flask and stir at room temperature for 24 h. After the reaction is completed, filter the reaction system using a sand core funnel and remove the solvent in vacuo. Recrystallize in dichloromethane and n-hexane solution to obtain a reddish brown solid, which is complex I3, 0.98 g (95%). Experimental data of α-diimine nickel complex I3: ESI-MS (m / z): [M-Br] + Calculate for C 56 H 42 BrN2NiCl2 + , 949.1262.

[0081] Embodiment 11

[0082] This embodiment provides a method for synthesizing α-diimine nickel complex I4. The steps include:

[0083] In a glove box with argon atmosphere, add α-diimine compound IV4 (0.59 g, 1.00 mmol), (DME)NiBr2 (0.31 g, 1.00 mmol), and 10 mL of anhydrous dichloromethane prepared in Example 1 to a 50 mL round-bottom flask and stir at room temperature for 24 h. After the reaction is completed, filter the reaction system using a sand core funnel and remove the solvent in vacuo. Recrystallize in dichloromethane and n-hexane solution to obtain a brown solid, which is complex I4, 0.71 g (88%). Experimental data of α-diimine nickel complex I4: ESI-MS (m / z): [M-Br] + Calculate for C 44 H 36 BrN2Ni + , 729.1415.

[0084] Example 12

[0085] This embodiment provides a method for synthesizing α-diimine nickel complex I5. The steps include:

[0086] In a glove box with argon atmosphere, add α-diimine compound IV5 (0.66 g, 1.00 mmol), (DME)NiBr2 (0.31 g, 1.00 mmol), and 10 mL of anhydrous dichloromethane prepared in Example 1 to a 50 mL round-bottom flask and stir at room temperature for 24 h. After the reaction is completed, filter the reaction system using a sand core funnel and remove the solvent in vacuo. Recrystallize in dichloromethane and n-hexane solution to obtain a reddish brown solid, which is complex I5, 0.82 g (93%). Experimental data of α-diimine nickel complex I5: ESI-MS (m / z): [M-Br] + Calculate for C 44 H 32 BrF4N2N i + , 801.1038.

[0087] Embodiment 13

[0088] This embodiment provides a method for synthesizing α-diimine nickel complex I6. The steps include:

[0089] In a glove box with argon atmosphere, add α-diimine compound IV6 (0.65 g, 1.00 mmol), (DME)NiBr2 (0.31 g, 1.00 mmol), and 10 mL of anhydrous dichloromethane prepared in Example 1 to a 50 mL round-bottom flask and stir at room temperature for 24 h. After the reaction is completed, filter the reaction system using a sand core funnel and remove the solvent in vacuo. Recrystallize in dichloromethane and n-hexane solution to obtain a brown solid, which is complex I6, 0.78 g (90%). Experimental data of α-diimine nickel complex I6: ESI-MS (m / z): [M-Br] + Calculate for C 48 H 44 BrN2Ni + , 785.2041.

[0090] Embodiment 14

[0091] This embodiment provides a method for synthesizing α-diimine nickel complex I7. The steps include:

[0092] In a glove box with argon atmosphere, add α-diimine compound IV7 (0.86 g, 1.00 mmol), (DME)NiBr2 (0.31 g, 1.00 mmol), and 10 mL of anhydrous dichloromethane prepared in Example 1 to a 50 mL round-bottom flask and stir at room temperature for 24 h. After the reaction is completed, filter the reaction system using a sand core funnel and remove the solvent in vacuo. Recrystallize in dichloromethane and n-hexane solution to obtain a brown solid, which is complex I7, 0.94 g (90%). Experimental data of α-diimine nickel complex I7: ESI-MS (m / z): [M-Br] + Calculate for C 48 H 32 F 12 N2 + , 1001.0911.

[0093] Application Examples 1 to 62 show that α-diimine nickel complexes with different electrical properties and steric substituents exhibit special catalytic characteristics in ethylene homopolymerization and ethylene and polar monomer copolymerization: within a certain pressure range, high-activity catalytic polymerization of ethylene is achieved to obtain high-performance polyolefin materials: narrow molecular weight distribution, low degree of branching, ultra-high molecular weight, polyolefin elastomers and polar polyethylene.

[0094] Application Example 1

[0095] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; after vacuuming the reactor, pass ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); after preheating and stirring at 30 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I1 (1 μmol) and adjust the ethylene pressure to 0.8 MPa, and stir the reaction for 10 minutes. After the reaction, the reactants were quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 1.

[0096] Application Example 2

[0097] The experimental process is the same as that of Application Example 1, except that the reaction temperature is changed from 30° C. to 50° C. The experimental results are shown in Table 1.

[0098] Application Example 3

[0099] The experimental process is the same as that of Application Example 1, except that the reaction temperature is changed from 30° C. to 70° C. The experimental results are shown in Table 1.

[0100] Application Example 4

[0101] The experimental process is the same as that of Application Example 1, except that the reaction temperature is changed from 30° C. to 90° C. The experimental results are shown in Table 1.

[0102] Application Example 5

[0103] The experimental process is the same as that of Application Example 1, except that the reaction temperature is changed from 30° C. to 120° C. The experimental results are shown in Table 1.

[0104] Application Example 6

[0105] Table 1

[0106]

[0107] In application example 1-6, at a pressure of 0.8 MPa and a reaction time of 10 min, the electron-donating methoxy group strengthened the linkage of the C=N bond, increased the electron cloud density of the metal center, and synergistically affected the chain walking and chain transfer processes with the large steric hindrance diphenylmethyl substituent and the rigid dibenzo-barrel ene skeleton, making it less affected by temperature and still active even at 140°C, showing the high thermal stability of the catalyst. Its molecular weight showed a trend of first increasing and then decreasing with increasing temperature, and both the molecular weight distribution and the degree of branching showed an increase, which was mainly due to the fact that diimine catalysts are prone to chain transfer and chain walking at high temperatures.

[0108] Application Example 7

[0109] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; after vacuuming the reactor, introduce ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); after preheating and stirring at 90 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I1 (1 μmol) and adjust the ethylene pressure to 0.8 MPa, and stir the reaction for 20 minutes. After the reaction, the reactants were quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 2.

[0110] Application Example 8

[0111] The experimental process is the same as that of Application Example 7, except that the reaction time is changed from 20 min to 30 min. The experimental results are shown in Table 2.

[0112] Application Example 9

[0113] The experimental process is the same as that of Application Example 7, except that the reaction time is changed from 20 min to 100 min. The experimental results are shown in Table 2.

[0114] Table 2

[0115]

[0116] Application Examples 4, 7-9 show the catalytic performance of I1 catalyst at different reaction times at 90°C and 0.8MPa. Due to the high thermal stability of I1, the catalyst has high activity at 90°C that other catalysts cannot achieve. Although the catalytic activity of I1 is slightly reduced when the reaction time is extended at 90°C, it still remains at 10 6 g·mol -1 ·h -1 It has high activity and its molecular weight is hardly affected by time at high temperature.

[0117] Application Example 10

[0118] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; evacuate the reactor, pass ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); preheat and stir at 30 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I2 (1 μmol) and adjust the ethylene pressure to 0.8 MPa, and stir for 10 minutes. After the reaction, the reactants were quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 3.

[0119] Application Example 11

[0120] The experimental process is the same as that of Application Example 10, except that the reaction temperature is changed from 30° C. to 50° C. The experimental results are shown in Table 3.

[0121] Application Example 12

[0122] The experimental process is the same as that of Application Example 10, except that the reaction temperature is changed from 30° C. to 70° C. The experimental results are shown in Table 3.

[0123] Application Example 13

[0124] The experimental process is the same as that of Application Example 10, except that the reaction temperature is changed from 30° C. to 90° C. The experimental results are shown in Table 3.

[0125] Table 3

[0126]

[0127] Application Example 10-13, pressure 0.8MPa, reaction time 10min, I2 catalyst exhibits high activity at low temperature due to the influence of the para-F substituent, but the activity decreases slightly at high temperature, and the molecular weight shows a trend of first increasing and then decreasing with temperature. This is because when the temperature rises, the chain transfer rate increases, resulting in a decrease in the molecular weight.

[0128] Application Example 14

[0129] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; after vacuuming the reactor, pass ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); after preheating and stirring at 30 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I2 (0.25 μmol) and adjust the ethylene pressure to 2.0 MPa, and stir the reaction for 10 minutes. After the reaction, the reactants were quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 4.

[0130] Table 4

[0131]

[0132] By adjusting the polymerization temperature, pressure and catalyst dosage, the I2 catalyst has the highest activity at 30°C. To further explore its reaction activity, the ethylene pressure was appropriately increased to allow polymerization at 2.0 MPa. In order to avoid excessive polymer pollution and damage to the reactor during the reaction, the catalyst dosage was appropriately reduced. Surprisingly, the catalyst activity can reach 1.0×10 8 g·mol -1 ·h -1 , currently few diimine catalysts can achieve such high activity.

[0133] Application Example 15

[0134] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; after vacuuming the reactor, pass ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); after preheating and stirring at 30 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I3 (1 μmol) and adjust the ethylene pressure to 0.8 MPa, and stir the reaction for 10 minutes. After the reaction is completed, the reactants are quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer is vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 5.

[0135] Application Example 16

[0136] The experimental process is the same as that of Application Example 15, except that the reaction temperature is changed from 30° C. to 50° C. The experimental results are shown in Table 5.

[0137] Application Example 17

[0138] The experimental process is the same as that of Application Example 15, except that the reaction temperature is changed from 30° C. to 70° C. The experimental results are shown in Table 5.

[0139] Application Example 18

[0140] The experimental process is the same as that of Application Example 15, except that the reaction temperature is changed from 30° C. to 90° C. The experimental results are shown in Table 5.

[0141] Table 5

[0142]

[0143] Application Examples 15-18 demonstrate the catalytic performance of I3 catalyst at different reaction temperatures with a pressure of 0.8 MPa and a reaction time of 10 min. Affected by the para-Cl substituent, it exhibits high activity at low temperatures, but its activity slightly decreases at high temperatures. In addition, the molecular weight shows a trend of first increasing and then decreasing with temperature. This is because as the temperature increases, the chain transfer rate increases, resulting in a decrease in the molecular weight.

[0144] Application Example 19

[0145] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; after vacuuming the reactor, pass ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); after preheating and stirring at 30 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I4 (1 μmol) and adjust the ethylene pressure to 0.8 MPa, and stir the reaction for 10 minutes. After the reaction is completed, the reactants are quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer is vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 6.

[0146] Application Example 20

[0147] The experimental process is the same as that of Application Example 19, except that the reaction temperature is changed from 30° C. to 50° C. The experimental results are shown in Table 6.

[0148] Application Example 21

[0149] The experimental process is the same as that of Application Example 19, except that the reaction temperature is changed from 30° C. to 70° C. The experimental results are shown in Table 6.

[0150] Application Example 22

[0151] The experimental process is the same as that of Application Example 19, except that the reaction temperature is changed from 30° C. to 90° C. The experimental results are shown in Table 6.

[0152] Table 6

[0153]

[0154] Application Examples 19-22 show the catalytic performance of I4 catalyst at different temperatures at a pressure of 0.8 MPa and a reaction time of 10 min. Compared with I1-3, the steric hindrance of the substituent of I4 catalyst is reduced, the chain transfer and chain walking rates are increased, the molecular weight is reduced, and the degree of branching is increased. I4 shows high activity at low temperatures, but the activity decreases slightly at high temperatures, and the molecular weight shows a trend of first increasing and then decreasing with temperature. This is because when the temperature rises, the chain transfer rate increases, resulting in a decrease in molecular weight.

[0155] Application Example 23

[0156] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; after vacuuming the reactor, pass ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); after preheating and stirring at 30 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I5 (1 μmol) and adjust the ethylene pressure to 0.8 MPa, and stir the reaction for 10 minutes. After the reaction, the reactants were quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 7.

[0157] Application Example 24

[0158] The experimental process is the same as that of Application Example 23, except that the reaction temperature is changed from 30° C. to 50° C. The experimental results are shown in Table 7.

[0159] Application Example 25

[0160] The experimental process is the same as that of Application Example 23, except that the reaction temperature is changed from 30° C. to 70° C. The experimental results are shown in Table 7.

[0161] Application Example 26

[0162] The experimental process is the same as that of Application Example 23, except that the reaction temperature is changed from 30° C. to 90° C. The experimental results are shown in Table 7.

[0163] Table 7

[0164]

[0165] Application Examples 23-26 show the catalytic performance of I5 catalyst at different temperatures at a pressure of 0.8 MPa and a reaction time of 10 min. Compared with I4, the substituent of I5 catalyst is 3,5-difluorophenyl, and F interacts with β-H on the polymer, resulting in a slight increase in molecular weight. I5 shows high activity at low temperatures, but slightly decreases at high temperatures, and the molecular weight shows a decreasing trend with temperature. This is because the electron-withdrawing F group is easily affected by temperature, resulting in an increase in chain transfer rate and a decrease in molecular weight.

[0166] Application Example 27

[0167] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; evacuate the reactor, pass ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); preheat and stir at 30 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I6 (1 μmol) and adjust the ethylene pressure to 0.8 MPa, and stir for 10 minutes. After the reaction, the reactants were quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 8.

[0168] Application Example 28

[0169] The experimental process is the same as that of Application Example 27, except that the reaction temperature is changed from 30° C. to 50° C. The experimental results are shown in Table 8.

[0170] Application Example 29

[0171] The experimental process is the same as that of Application Example 27, except that the reaction temperature is changed from 30° C. to 70° C. The experimental results are shown in Table 8.

[0172] Application Example 30

[0173] The experimental process is the same as that of Application Example 27, except that the reaction temperature is changed from 30° C. to 90° C. The experimental results are shown in Table 8.

[0174] Table 8

[0175]

[0176] Application Examples 27-30 show the catalytic performance of I6 catalyst at different temperatures at a pressure of 0.8 MPa and a reaction time of 10 min. Compared with I4, the substituent of I6 catalyst is 3,5-dimethylphenyl. The introduction of two methyl groups increases the steric hindrance, resulting in a slight increase in molecular weight. I6 shows high activity at low temperatures, but slightly decreases at high temperatures, and the molecular weight shows a decreasing trend with temperature, because the chain transfer rate increases and the molecular weight decreases due to high temperature.

[0177] Application Example 31

[0178] Under the anhydrous and oxygen-free conditions in the glove box, add anhydrous toluene (48 mL) to a 100 mL thick-walled quartz dish and place it in the intelligent olefin polymerization device; after vacuuming the reactor, pass ethylene to saturation, and add AlEt2Cl (0.6 mL, 1M intoluene); after preheating and stirring at 30 ° C, add a dichloromethane (2 mL) solution of α-diimine nickel complex I7 (1 μmol) and adjust the ethylene pressure to 0.8 MPa, and stir the reaction for 10 minutes. After the reaction, the reactants were quenched with an ethanol solution containing 5% hydrochloric acid. After precipitation, filtration, and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 9.

[0179] Application Example 32

[0180] The experimental process is the same as that of Application Example 31, except that the reaction temperature is changed from 30° C. to 50° C. The experimental results are shown in Table 9.

[0181] Application Example 33

[0182] The experimental process is the same as that of Application Example 31, except that the reaction temperature is changed from 30° C. to 70° C. The experimental results are shown in Table 9.

[0183] Application Example 34

[0184] The experimental process is the same as that of Application Example 31, except that the reaction temperature is changed from 30° C. to 90° C. The experimental results are shown in Table 9.

[0185] Table 9

[0186]

[0187]

[0188] Application Examples 31-34 show the catalytic performance of I7 catalyst at different temperatures at a pressure of 0.8 MPa and a reaction time of 10 min. The substituent of I7 catalyst is 3,5-ditrifluoromethylphenyl, and trifluoromethyl is a strong electron-withdrawing substituent, which can make I7 show high activity at low temperatures, but the activity slightly decreases at high temperatures, and the molecular weight shows a decreasing trend with temperature, which is because the chain transfer rate increases and the molecular weight decreases due to high temperature.

[0189] The above 34 application examples are ethylene homopolymerization.

[0190] Among the existing α-diimine catalysts that can produce ultra-high molecular weight, J. Catal., 2020, 390, 30-36, CN111548285A discloses an α-diimine catalyst with a double-layer space strategy, which can be used to prepare ultra-high molecular weight polyethylene by combining with methylaluminoxane activator, with a molecular weight of up to 467×10 4 g·mol -1 Organometallics, 2022, 41, 124-132, CN 114349658A uses the dual steric hindrance effect to prepare a catalyst with higher stability, which can obtain ultra-high branched polyethylene (M w =127.3 g mol -1 , branching degree: 80-150 / 1000C); Polym.Chem., 2023, 14, 183-190, a catalyst combining a large sterically hindered diphenylmethyl substituent and a benzocycloalkyl group was also designed by the research group, further improving the catalytic activity (10 7 g mol -1 h -1 ), and prepared ultra-high molecular weight polyethylene (M w =185×10 4 g mol -1 ), but also leads to a higher molecular weight distribution; Polymer, 2024, 293, 126690-126703 The synergistic effect of stereo substituents and electronic substituents improves the performance of the catalyst. The introduction of three methoxy groups significantly improves the chain growth rate and promotes the synthesis of ultra-high molecular weight polyethylene (M w =126×10 4 g mol -1 ).

[0191] Compared with the above catalysts, I1-7 showed super high activity in ethylene homopolymerization (activity ≥10 at 30-90°C). 7 g mol -1 h -1), has excellent high temperature resistance (still highly active at 120°C), which is unattainable by the above catalysts, and can produce ultra-high molecular weight polyethylene (79-833×10 4 g·mol -1 ), and the molecular weight distribution is narrow It has a relatively low degree of branching (15-41 / 1000C). It can be seen that even under relatively harsh high temperature conditions, it can still achieve catalytic performance that the above catalysts cannot achieve.

[0192] Application Example 35

[0193] Under the anhydrous and oxygen-free conditions of the glove box, anhydrous toluene (20 mL) and AlEt2Cl (3 mL, 1 M in toluene) were added to a 350 mL thick-walled pressure bottle in sequence. The pressure bottle was taken out of the glove box and connected to the ethylene gas line to evacuate and then ethylene was introduced to saturation. After preheating and stirring at 0.4 MPa and 30 ° C for 10 min, a solution of 10-undecenoic acid methyl ester (0.50 M) and α-diimine nickel complex I1 (5 μmol) in dichloromethane (2 mL) was added and stirred for 30 min. After the reaction was completed, the reaction was terminated with ethanol containing 5% hydrochloric acid. After precipitation, filtration and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 10.

[0194] Application Example 36

[0195] The experimental process is the same as that of Application Example 35, except that catalyst I1 is replaced by I2. The experimental results are shown in Table 10.

[0196] Application Example 37

[0197] The experimental process is the same as that of Application Example 35, except that catalyst I1 is replaced by I3. The experimental results are shown in Table 10.

[0198] Table 11

[0199]

[0200] Application Example 38

[0201] Under the anhydrous and oxygen-free conditions in the glove box, anhydrous toluene (20 mL) and AlEt2Cl (3 mL, 1 M in toluene) were added to a 350 mL thick-walled pressure bottle in sequence. The pressure bottle was taken out of the glove box and connected to the ethylene gas line to evacuate and then ethylene was introduced to saturation. After preheating and stirring at 0.4 MPa and 30 ° C for 10 min, 6-chloro-1-hexene (0.50 M) and α-diimine nickel complex I1 (5 μmol) in dichloromethane (2 mL) were added and stirred for 30 min. After the reaction was completed, the reaction was terminated with ethanol containing 5% hydrochloric acid. After precipitation, filtration and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 12.

[0202] Application Example 39

[0203] The experimental process is the same as that of Application Example 38, except that catalyst I1 is replaced by I2. The experimental results are shown in Table 11.

[0204] Application Example 40

[0205] The experimental process is the same as that of Application Example 38, except that catalyst I1 is replaced by I3. The experimental results are shown in Table 11.

[0206] Table 11

[0207]

[0208] Application Example 41

[0209] Under the anhydrous and oxygen-free conditions in the glove box, anhydrous toluene (20 mL) and AlEt2Cl (3 mL, 1 M in toluene) were added to a 350 mL thick-walled pressure bottle in sequence. The pressure bottle was taken out of the glove box and connected to the ethylene gas line to evacuate and then ethylene was introduced to saturation. After preheating and stirring at 0.4 MPa and 30 ° C for 10 min, a dichloromethane (2 mL) solution of vinyltrimethoxysilane (0.50 M) and α-diimine nickel complex I1 (5 μmol) was added and stirred for 30 min. After the reaction was completed, the reaction was terminated with ethanol containing 5% hydrochloric acid. After precipitation, filtration and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 12.

[0210] Application Example 42

[0211] The experimental process is the same as that of Application Example 41, except that catalyst I1 is replaced by I2. The experimental results are shown in Table 12.

[0212] Application Example 43

[0213] The experimental process is the same as that of Application Example 41, except that catalyst I1 is replaced by I3. The experimental results are shown in Table 12.

[0214] Table 12

[0215]

[0216] Application Example 44

[0217] Under the anhydrous and oxygen-free conditions in the glove box, anhydrous toluene (20 mL) and AlEt2Cl (3 mL, 1 M in toluene) were added to a 350 mL thick-walled pressure bottle in sequence. The pressure bottle was taken out of the glove box and connected to the ethylene gas line to evacuate and then ethylene was introduced to saturation. After preheating and stirring at 0.4 MPa and 30 ° C for 10 min, methyl acrylate (0.50 M) and α-diimine nickel complex I1 (5 μmol) in dichloromethane (2 mL) were added and stirred for 30 min. After the reaction was completed, the reaction was terminated with ethanol containing 5% hydrochloric acid. After precipitation, filtration and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 13.

[0218] Application Example 45

[0219] The experimental process is the same as that of Application Example 44, except that methyl acrylate (0.50 M) is replaced by methyl 5-norbornene-2-carboxylate (0.10 M). The experimental results are shown in Table 13.

[0220] Application Example 46

[0221] The experimental process is the same as that of Application Example 44, except that methyl acrylate (0.50 M) is replaced by allyl acetate (0.25 M). The experimental results are shown in Table 13.

[0222] Table 13

[0223]

[0224]

[0225] Application Example 47

[0226] Under the anhydrous and oxygen-free conditions of the glove box, anhydrous toluene (20 mL) and AlEt2Cl (3 mL, 1 M in toluene) were added to a 350 mL thick-walled pressure bottle in sequence. The pressure bottle was taken out of the glove box and connected to the ethylene gas line to evacuate and then ethylene was introduced to saturation. After preheating and stirring at 0.2 MPa and 30 ° C for 10 min, 1-octene (0.5 M) and α-diimine nickel complex I7 (10 μmol) in dichloromethane (2 mL) were added and stirred for 30 min. After the reaction was completed, the reaction was terminated with ethanol containing 5% hydrochloric acid. After precipitation, filtration and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 14.

[0227] Application Example 48

[0228] The experimental process is the same as that of Application Example 47, except that 1-octene (0.5 M) is replaced by 1-octene (1.0 M). The experimental results are shown in Table 14.

[0229] Application Example 49

[0230] The experimental process is the same as that of Application Example 47, except that 1-octene (0.5 M) is replaced by 1-octene (3.0 M). The experimental results are shown in Table 14.

[0231] Table 14

[0232]

[0233] Application Examples 47-49 show that under the conditions of 0.2 MPa pressure and 30 min reaction time, I7 is polymerized with 1-octene of different concentrations to produce high-end polyethylene thermoplastic elastomer POE, and as the concentration of 1-octene increases, the elastic recovery rate of POE also increases significantly ( Figure 7-10 ). 400 μmol / L of catalyst I7 was polymerized with 3.0 M 1-octene at 30°C and 0.2 MPa for 30 min to prepare high-performance polyethylene (POE), whose strain performance could reach up to 2300% and elastic recovery rate could reach 71%.

[0234] Application Example 50

[0235] Under the anhydrous and oxygen-free conditions of the glove box, anhydrous toluene (20 mL) and AlEt2Cl (3 mL, 1 M in toluene) were added to a 350 mL thick-walled pressure bottle in sequence. The pressure bottle was taken out of the glove box and connected to the ethylene gas line to evacuate and then ethylene was introduced to saturation. After preheating and stirring at 0.2 MPa and 30 ° C for 10 min, a dichloromethane (2 mL) solution of 10-undecene-1-ol (0.10 M) and α-diimine nickel complex I7 (10 μmol) was added and stirred for 30 min. After the reaction was completed, the reaction was terminated with ethanol containing 5% hydrochloric acid. After precipitation, filtration and washing, the polymer was vacuum dried at 50 ° C to constant weight to obtain a polymerization product. The specific experimental results are shown in Table 15.

[0236] Application Example 51

[0237] The experimental process is the same as that of Application Example 50, except that 10-undecene-1-ol (0.10 M) is replaced by 9-decene-1-ol (0.10 M). The experimental results are shown in Table 15.

[0238] Application Example 50

[0239] The experimental process is the same as that of Application Example 46, except that 10-undecene-1-ol (0.10 M) is replaced with 5-hexene-1-ol (0.10 M). The experimental results are shown in Table 15.

[0240] Application Example 50

[0241] The experimental process is the same as that of Application Example 46, except that 10-undecene-1-ol (0.10 M) is replaced with butenoic acid (0.10 M). The experimental results are shown in Table 15.

[0242] Table 15

[0243]

[0244] It can be seen from Application Examples 1 to 34 that the catalysts I1 to 7 of the present invention can prepare polyethylene with high catalytic activity and can prepare ultra-high molecular weight polyethylene with a relatively low degree of branching. During olefin polymerization, I1-I7 utilize the dibenzo-barrelene skeleton with large steric hindrance to shield the steric hindrance on the back of the metal. At the same time, the ortho-aromatic substituents with large stereoscopic space inhibit chain transfer, reduce the molecular weight distribution of the polymer, and greatly increase the molecular weight of the polymer. The ultra-high molecular weight polyethylene catalyzed by I2 is even as high as 833.3×10 4 g·mol -1 , before this, catalysts that can prepare such high molecular weight polyethylene are extremely rare. As the temperature increases, the introduction of these large sterically hindered aromatic substituents greatly enhances the stability of the nickel complex; and I1 can still be highly active at 120°C with a concentration of 7.32×10 6 g·mol -1 ·h -1 The catalyst catalyzes ethylene polymerization, which fully proves the high thermal stability of this type of catalyst. Compared with I1, I4, and I6, I2, I3, I5, and I7 introduce electron-withdrawing groups at different positions of different benzene rings, which greatly improves the activity of the catalyst. In addition, by adjusting the temperature, pressure, and other conditions of the polymerization reaction, the maximum activity of the catalyst can reach 1.0×10 8 g·mol -1 ·h -1 (Application Example 14).

[0245] The polymers prepared by I1-3 are ultra-high molecular weight polyethylene thermoplastic elastomers. Through mechanical property tests on polyethylene, it is found that the polyethylene prepared by the catalyst has good mechanical properties and tensile strength ( Figure 4-6 The stress value of the ultra-high molecular weight thermoplastic elastomer prepared by I1 at 50°C can reach 43MPa, and the polyethylene prepared by I2 at 70°C can maintain an ultra-high molecular weight (833.3×10 4 g·mol -1) and has good tensile properties (maximum strain up to 770%) ( Figure 4-6 ). By introducing different electronic groups at the ortho or para position of benzene, the elimination of β-H can be well suppressed, thereby improving the activity and molecular weight of the catalyst.

[0246] It can be seen from Application Examples 35 to 54 that the catalysts I1, I2, I3 and I7 of the present invention can all catalyze the preparation of polar functionalized polyolefins with high activity under certain conditions, with the highest activity reaching 13.34×10 5 g·mol -1 ·h -1 (Application Example 48), the insertion ratio of catalyst I7 copolymerized with polar monomers is as high as 1.22% (Application Example 51). In addition, I7 can also copolymerize with 1-octene to form an industrially available co-solvent blending agent POE (polyolefin elastomer). The mechanical properties of the POE material were tested and found to have excellent strain (2300%) and elastic recovery (71%) ( Figure 7-10 ).

[0247] The experimental results show that the α-diimine nickel complex provided by the present invention has extremely high catalytic activity for olefin polymerization, can produce polyolefin materials with controllable ultrahigh molecular weight, and can produce functionalized high-end polyolefins.

[0248] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. α-Diimine nickel complex having the chemical structure shown in formula (I): Where R 1 is diphenylmethyl, phenyl, 3,5-difluorophenyl, 3,5-dimethylphenyl, 3,5-ditrifluoromethylphenyl, R 2 It is a type of halogen or alkoxy.

2. The α-diimine nickel complex according to claim 1, characterized in that The structural formula is as follows:

3. The method for synthesizing the α-diimine nickel complex according to claim 1 or 2, characterized in that: The following steps are involved: (1) The dibenzo-barrelene represented by formula (II) and the aniline compound represented by formula (III) are subjected to a condensation reaction at 130° C. for 12 to 36 hours under the catalysis of a first catalyst to generate an α-diimine compound represented by formula (IV). The reaction scheme is as follows: Where R 1 is one of diphenylmethyl, phenyl, 3,5-difluorophenyl, 3,5-dimethylphenyl, 3,5-ditrifluoromethylphenyl, R 2 is one of halogen and alkoxy; (2) reacting the α-diimine compound represented by formula (IV) with (DME)NiBr2 at 0 to 45°C for 1 to 50 hours to obtain an α-diimine nickel complex having a chemical structure represented by formula (I); The first catalyst is zinc dichloride.

4. The synthesis method according to claim 3, characterized in that: In step (1), the molar ratio of the dibenzo-barrelene represented by formula (II) to the aniline compound represented by formula (III) is 1:(2-3).

5. The synthesis method according to claim 3, characterized in that: In step (2), the molar ratio of the α-diimine compound to (DME)NiBr2 is 1:(0.1-6).

6. Use of the α-diimine nickel complex according to claim 1 or 2 in the synthesis of polyolefins, characterized in that: α-Diimine nickel complexes are used as ultra-high activity and highly thermally stable catalysts to catalyze ethylene polymerization to prepare ultra-high molecular weight polyethylene thermoplastic elastomers and POE materials.

7. The use according to claim 6, characterized in that: The terminal olefin-containing compound is brought into contact with an α-diimine nickel complex having a chemical structure shown in formula (I) and an alkyl aluminum reagent, and the terminal olefin-containing compound undergoes a catalyst homopolymerization reaction. The homopolymerization reaction is carried out in an organic solvent. The amount of the α-diimine nickel complex used is 5 to 40 μmol / L. The homopolymerization reaction temperature is 0° C. to 150° C., the pressure is 0.1 to 2.0 MPa, and the reaction time is 0.05 to 3.00 hours.

8. The use according to claim 6, characterized in that: A terminal olefin compound and a polar monomer are contacted with an α-diimine nickel complex having a chemical structure shown in formula (I) and an alkyl aluminum reagent, and the terminal olefin compound and the polar monomer undergo copolymerization reaction, wherein the copolymerization reaction temperature is 0 to 50° C., the copolymerization reaction pressure is 0.1 to 1 MPa, and the reaction time is 0.05 to 3.00 hours; the concentration of the α-diimine nickel complex is 200 to 400 μmol / L, and the monomer concentration is 0.1 to 3.0 M; the polar monomer refers to an α-olefin containing a heteroatom, including at least one of 10-undecenoic acid methyl ester, vinyltrimethoxysilane, 1-octene, 6-chloro-1-hexene, 10-undecenol, methyl acrylate, propylene acetate, and methyl norbornene.

9. The use according to claim 7, characterized in that: The best catalytic effect can be obtained when the concentration of α-diimine nickel complex is 20 μmol / L, the temperature of homopolymerization is 30°C, the pressure is 0.8 MPa, and the reaction time is 10 minutes.

10. The use according to claim 8, characterized in that: 400 μmol / L of catalyst I7 can be polymerized with 3.0 M 1-octene at 30°C and 0.2 MPa for 30 min to prepare high-performance polyethylene (POE), with a strain performance of up to 2300% and an elastic recovery rate of 71%.

Citation Information

Patent Citations

  • Polymerization method for catalyzing olefin by nickel-diimine catalytic system

    CN103288985A

  • Olefin polymerization catalyst as well as preparation method and application method thereof

    CN105482000A

  • Asymmetric alpha-diimine nickel (II) complex containing phenanthrenequinone fluoride skeleton and preparation method and application of asymmetric alpha-diimine nickel (II) complex

    CN109762026A

  • Fluorine-containing alpha-diimine nickel coordination compounds for preparing polyolefin elastomer, intermediate, preparation method and application thereof

    CN111303215A

  • Alpha-diimine ligand compound, complex and preparation method of polyolefin lubricating oil base oil

    CN111377827A